Study of Small-Scale Capture Fisheries in West Sulawesi Waters “Case Study of Large Pelagic Fishing Rod In Mamuju Regency” - Roswati, Roswati; Najamuddin, Najamuddin; Nelwan, Alfa Filep Petrus (International Journal of Environment, Agriculture and Biotechnology, 2023)
Mamuju Regency, West Sulawesi Province, has the potential for pelagic fish, especially large pelagic fish, namely tuna, skipjack and cob, which are very prospective. The majority of fishermen in Mamuju Regency use fishing rods to catch large pelagic fish. Fishing rod fishermen with a large pelagic catch target are in Mamuju Regency, Simboro District, precisely in Sumare Village but currently it is known that there has been a decrease in the number of fishing rod fishermen in Mamuju Regency since the last 5 years experiencing a decrease in production. This study aims to determine the status of small-scale capture fisheries in a sustainability perspective according to ecological, technological, social and economic dimensions for small-scale fisheries in Mamuju Regency, and recommendations for sustainable capture fisheries. The study was conducted using qualitative methods using Rapfish analysis to determine the sustainability of fishing efforts. The results showed the highest dimensions in fish resources (70.13) and fishing technology (50.06) which means quite sustainable (good) while in the social dimension (38.47) and economic dimension (28.75) in the bad category which means there needs to be special attention in handling.